Citizenship and state-building in East Timor - Jerónimo, Patrícia (2011)
One of the most fundamental state prerogatives is to decide who belongs to the political community. When East Timor became independent from Indonesia on May 20, 2002, the Constitution of the new country set the criteria for attributing Timorese citizenship by origin. The constitutional provision on citizenship combines the traditional jus soli and jus sanguinis principles in such a way that grants easy access to Timorese citizenship by origin. This generosity may be explained by the fact that East Timor is a small and poor country with a vast diaspora, although recent legal developments suggest that the Constituent Assembly might have said more than it intended. The clarification of the scope of the constitutional provision is extremely important, not only for symbolic reasons (connection between citizenship and national identity), but also for its practical consequences, given that many fundamental rights under the Constitution (including the right to own land) are exclusive to Timorese citizens.